PENYULUHAN CUCI TANGAN PAKAI SABUN DI SDN 128 PEKANBARU KELURAHAN RANTAU PANJANG PEKANBARU - Anugerah, M Fajar; ., Husnah; Yulianti, Wita; Juariah, Siti (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Health behavior problems in school-age children are related to personal hygiene and the environment. One health problem is the lack of awareness of washing hands with soap. The purpose of this study was to determine the knowledge of students at 128 Rumbai Pekanbaru. This type of research is qualitative research that intends to understand the phenomena about what is experienced by research subjects such as behavior, perception, motivation, ways of description in the form of words and language, in a special natural context and by utilizing various natural methods. The research sample was elementary school students in 128 tassel Pekanbaru. The results showed that the majority of respondents did not have good knowledge on how to wash hands properly.